2021
DOI: 10.1002/brb3.2301
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and etiological profile of epilepsy at the regional hospital center of Tahoua (Niger): A 4‐year retrospective study

Abstract: Objective: We aimed to evaluate epilepsy management at the regional hospital center (RHC) of Tahoua (Niger) to determine the intrahospital deficiencies to optimize to improve the management of people with epilepsy.Methods: A descriptive retrospective study was carried out at the Psychiatric Unit of the RHC of Tahoua between January 1, 2016 and December 31, 2019. We collected from the registers of consultation all patients followed by nurse technicians in mental health for epilepsy whose diagnosis was made by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, two hospital-based studies on epilepsy have been published. 4,5 The first study was conducted in Niamey in a tertiary care center in a neurological unit and reported a hospital prevalence of 29.5%. 4 In the above study, the diagnosis of epilepsy was considered in case of at least two unprovoked (or reflex) seizures occurring more than 24 h apart or one unprovoked (or reflex) seizure in individuals who have risk factors such as cerebrovascular disease, central nervous system infection, and traumatic brain injury according to the 2014 revised definition of epilepsy of ILAE Official report.…”
Section: Incidence and Prevalencementioning
confidence: 99%
See 4 more Smart Citations
“…However, two hospital-based studies on epilepsy have been published. 4,5 The first study was conducted in Niamey in a tertiary care center in a neurological unit and reported a hospital prevalence of 29.5%. 4 In the above study, the diagnosis of epilepsy was considered in case of at least two unprovoked (or reflex) seizures occurring more than 24 h apart or one unprovoked (or reflex) seizure in individuals who have risk factors such as cerebrovascular disease, central nervous system infection, and traumatic brain injury according to the 2014 revised definition of epilepsy of ILAE Official report.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…7 The second study was conducted in Tahoua in a secondary care center in a psychiatric unit and reported a hospital prevalence of 12.2%. 5 The diagnosis of epilepsy was considered in the case of repetition of epileptic seizures over time in this study. The mean hospital prevalence was estimated to be 24.2% (95% CI: 23.2-25.2) (Table 1).…”
Section: Incidence and Prevalencementioning
confidence: 99%
See 3 more Smart Citations